KOMUNIKASI PEMASARAN D’PENYETZ, DALAM MENARIK MINAT KONSUMEN DI PEKANBARU - Rahmadhon S, Febri; Yesicha, Chelsy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The city of Pekanbaru is a strategic area where the population is increasing and becoming a metropolitan city. Of course there have been many mushrooming restaurants in Pekanbaru such as: Pondok Patin H.M. Yunus, Sushi Tei, Savory Pondok, Buana City, Delicious, Kian Wee Fish, Ta Wan Restaurant, and so on. The presence of other restaurants as Competitors who sell a variety of Indonesian specialties make Restoran D'penyet Pekanbaru must strive to increase the number of consumers in addressing the problem of decreasing consumers. Therefore researchers are interested in conducting research with the aim of finding out the marketing communication strategy of D'penyet Pekanbaru Restaurant in attracting consumer interest through sales promotion activities, which are carried out by loading new menus, publicity and public relations, direct marketing, internet marketing. The research conducted qualitative methods, namely data collection obtained based on the reality of field data through observation, interviews, and documentation. The subjects of this study were 1 manager and 2 consumers of the Pekanbaru d'penyetz restaurant who were selected using the pursosiv sampling technique. To analyze the results of this study using interactive data analysis techniques, while the technique of checking the validity of the data through an extension of participation and triangulation.He results of this study indicate that the marketing communication strategy of restaurant d'penyetz Pekanbaru in attracting consumer interest through sales promotion activities is a menu promo and discounts on the big day. Personal selling activities make direct presentations. Through community relations activities, namely by making press releases, and socializing directly with consumers, and potential consumers of restaurants d'penyetz pekanbaru. And with Internet marketing media activities use media using social Facebook, Instagram and WhatsApp